PENGARUH PEMBERIAN MADU SIALANG DENGAN DOSIS BERBEDA TERHADAP JANTANISASI IKAN CUPANG (Betta sp) - Rendy Alsiawan; Muhammad Hasby (UIR Press, 2022)
The aim of this study is to determine the effect of giving sialang honey with different doses on the monetization of Betta fish (Betta sp). and to know the best dose for male betta fish. The method used in this study is an experimental method using a completely randomized design (CRD) with 5 treatments and 3 replications, namely: P0 (control), P1 (5 ml/L), P2 (6 ml/L), P3 (7 ml /L) and P4 (8 ml/L). The test fish used was obtained from a betta fish seller in Jalan Pasir Putih. The container used was a jar with a capacity of 10 liters as many as 15 pieces. The best results were obtained at P4 (8 ml/L) with the percentage of male sex directing success of 81.79%. The highest larval survival was found in treatment P4 (8 ml/L) at 78.89%. The results of the measurement of water quality parameters during the study temperature ranged from 28-32oC, pH 6.5-7, ammonia 0.08-0.58 ppm, DO 4.8-5.4 ppm. The brightness was 30-60 cm and the depth was between 0.9-1.1 cm.